2021
DOI: 10.1161/jaha.120.019834
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year Outcomes After Drug‐Eluting Stents or Bypass Surgery for Left Main Coronary Disease in Patients With and Without Diabetes Mellitus: The PRECOMBAT Extended Follow‐Up Study

Abstract: Background Several trials reported differential outcomes after percutaneous coronary intervention with drug‐eluting stents (DES) and coronary‐artery bypass grafting (CABG) for multivessel coronary disease according to the presence of diabetes mellitus (DM). However, it is not well recognized how DM status affects very‐long‐term (10‐year) outcomes after DES and CABG for left main coronary artery disease. Methods and Results In the PRECOMBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…After the removal of duplicate records and studies based on title/abstract review, 30 remained and were fully reviewed for the inclusion and exclusion criteria. Four RCTs met all inclusion criteria (EXCEL, NOBLE, PRECOMBAT, and SYNTAX) 7,16–19 . A nonoverlapping population of 1080 patients was included, of whom 553 (51.2%) underwent PCI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the removal of duplicate records and studies based on title/abstract review, 30 remained and were fully reviewed for the inclusion and exclusion criteria. Four RCTs met all inclusion criteria (EXCEL, NOBLE, PRECOMBAT, and SYNTAX) 7,16–19 . A nonoverlapping population of 1080 patients was included, of whom 553 (51.2%) underwent PCI.…”
Section: Resultsmentioning
confidence: 99%
“…Four RCTs met all inclusion criteria (EXCEL, NOBLE, PRECOMBAT, and SYNTAX). 7,[16][17][18][19] A nonoverlapping population of 1080 patients was included, of whom 553 (51.2%) underwent PCI. 1.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 475 records and 13 studies were considered relevant and then retrieved. Among them, 4 RCTs [BEST (NCT05125367 and NCT00997828) FREEDOM (NCT00086450), PRECOMBAT (NCT03871127 and NCT00422968) and SYNTAX (NCT03417050) (20)(21)(22)(23)] met the eligibility criteria and were included in the final analysis. The PRISMA Flow Chart of study selection is shown in Supplemental Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…This is still controversial despite recent data. Looking at specific subsets of patients like those with the left main disease, some very recent data from Jeong et al 14 suggest that there are no significant differences between DES and CABG with respect to the incidences of MACCE, serious composite outcome, and all‐cause mortality in patients with and without diabetes mellitus with LMCA disease although authors state that their sample size could be a limitation. Furthermore, Ono et al 15 just a few days ago highlight in this extended follow‐up of the SYNTAX trial 16 that there were no significant differences at 10 years in all‐cause death and estimated life expectancy between PCI and CABG in the elderly (>70 years).…”
mentioning
confidence: 99%